Desenhar um romance - projecto do Centro de Enoturismo para a Quinta da Aveleda, Penafiel - Pedro Emanuel Sousa Colaço Leal (2015)
The Wine Tourism Center Project for Quinta da Aveleda directed this research to the study of drawing. This tool was essential for the architecture design process and is the subject of this dissertation. The research is divided into two parts: irstly, the theoretical inquiry creates the basis for the analysis of the process design achieved during the Wine Tourism Center project. Secondly, the data structured in instances assigns clarity and rigor to architectural deisgn issues arising from the drawing process. The drawing experience resulted in looking for the underlying drawing method. Drawing is the architectural gestation. In its turn, in the dissertation, drawing is interpreted as a spatial experience and as a simulation of reality. Bether said it is a way of thinking and it´s where we see the project reasoning. In this context, the morphological variety of the drawing promotes the debate of several design themes that are interpreted by drawing in three instances: In the Perceptual Instance issues of space, scale, program and site produce analysis drawing. In the second instance of architectural design, the Conceptual Instance, the study of form results in persistent and abstract drawings. In the last instance, Operational Instance, the drawing communicate te project others. In short, drawing, is the thought of an idea that later materializes itself in the construction. In this context, this visual tool's main feature is its agile and spontaneous way in translating ideas. Drawing is the materialization of reasoning.